Brief recommendations on the management of adult patients with familial hypercholesterolemia during the COVID-19 pandemic. (August 2020) - Banach, Maciej; Penson, Peter E.; Fras, Zlatko; Vrablik, Michal; Pella, Daniel; Reiner, Željko; Nabavi, Seyed Mohammad; Sahebkar, Amirhossein; Kayikcioglu, Meral; Daccord, Magdalena; ,
Abstract: Individuals with Familial Hypercholesterolaemia (FH) are at very high risk of cardiovascular disease, which is associated with poor outcomes from coronavirus infections. COVID-19 puts strain on healthcare systems and may impair access to routine FH services. On behalf of the International Lipid Expert Panel (ILEP) and the European FH Patient Network (FH Europe), we present brief recommendations on the management of adult patients with FH during the COVID-19 pandemic. We discuss the implications of COVID-19 infections for FH patients, the importance of continuing lipid-lowering therapy where possible, issues relating to safety monitoring and service delivery. We summarise the evidence for additional benefits of statins and other lipid-lowering drugs during viral infections. The recommendations do not override in any way the individual responsibility of physicians to make appropriate and accurate decisions taking into account the condition of a given patient and the doses, rules, and regulations applicable to drugs and devices at the time of their prescription/use.